Valuing the Unpaid Contribution of Community Health Volunteers to Mass Drug Administration Programs. (29th August 2018) - Turner, Hugo C; Toor, Jaspreet; Bettis, Alison A; Hopkins, Adrian D; Kyaw, Shwe Sin; Onwujekwe, Obinna; Thwaites, Guy E; Lubell, Yoel; Fitzpatrick, Christopher
Abstract: Community health volunteers (CHVs) are being used within a growing number of healthcare interventions, and they have become a cornerstone for the delivery of mass drug administration within many neglected tropical disease control programs. However, a greater understanding of the methods used to value the unpaid time CHVs contribute to healthcare programs is needed. We outline the two main approaches used to value CHVs' unpaid time (the opportunity cost and the replacement cost approaches). We found that for mass drug administration programs the estimates of the economic costs relating to the CHVs' unpaid time can be significant, with the averages of the different studies varying between US0.05 and 0.16 per treatment. We estimated that the time donated by CHVs' to the African Programme for Onchocerciasis Control alone would be valued between US60 and 90 million. There is a need for greater transparency and consistency in the methods used to value CHVs' unpaid time. Abstract : The global health community needs a greater understanding of the opportunity costs community health volunteers incur when contributing to healthcare programs. Focusing on mass drug administration programs as an example, we found that these costs can be significant.